Ruthenium catalysts for hydrogenation of biomass-based levulinic acid for efficient γ-valerolactone synthesis - Kejia Zhang; Jieni Wang; Yijun Tian; Shuqin Zhang; Season S. Chen; Leichang Cao; Jinglai Zhang; James H. Clark; Shicheng Zhang (iScience)
Summary: Biomass is the only abundant and concentrated carbon source for renewable fuels and chemicals. Among biomass platform molecules, γ-valerolactone (GVL) has a wide range of applications. Supported Ru catalysts show the most promising catalytic performance in the selective hydrogenation of levulinic acid (LA) to GVL and attract much research in recent years. In this article, recent advances in the synthesis of GVL from biomass-derived LA by hydrogenation are discussed. The routes and methods for the preparation of GVL by selective hydrogenation of LA are summarized focusing on the different supports (carbon, oxides, and others) by comparing the differences of catalytic systems. Emerging novel catalyst design strategies and auxiliary reaction processes (microwave-assisted catalysis and in situ formation of Ru catalyst, etc.) as well as future prospects in terms of sustainability are also proposed to enable a sustainable and industrially viable synthesis of GVL from biomass-based LA.